Santa clause 2 [videorecording (DVD)] - Lembeck, Michael; Allen, Tim, 1953-; Reinhold, Judge, 1957-; Crewson, Wendy (Disney DVD., 2003)
Scott Calvin has been Santa Claus for the past eight years, and his elves consider him the best ever. But Santa's world is turned upside down when his son gets on the naughty list, and if Scott doesn't marry soon, he'll stop being Santa forever.